Spectral energy distribution for GJ406 - Lyubchik, Yu.; Pavlenko, Ya.V.; Jones, H.R.A.; Tennyson, J.; Pinfield, D. (Кинематика и физика небесных тел, 2005)
We present results of modelling the bulk of the spectral energy distribution (0.45–5 μm) for GJ406 (M6V). Synthetic spectra were calculated using the NextGen model atmospheres of Hauschildt et al. [6] and the incorporate line lists for H2O, TiO, CrH, FeH, CO, MgH molecules as well as the VALD line list of atomic lines. The computed water partition function is in a good agreement with the one obtained by Vidler & Tennyson [14]. A comparison of synthetic and observed spectra gives Teff = 2900 ± 100 K for this late M-dwarf. The William Herschel Telescope and United Kingdom Infrared Telescope are operated for the Particle Physics and Astronomy Research Council (PPARC). ISO is an ESA project with the participation of ISAS and NASA funded from member states. HST is a NASA project funded in part by ESA. This work was partially supported by a PPARC visitors grants from PPARC and the Royal Society. YP’s studies are partially supported by a Small Research Grant from American Astronomical Society. This research has made with the use of the SIMBAD database, operated at CDS, Strasbourg, France.